Stable water isotopes in precipitation over western Cuba - Hernández, Yeleine Almoza (2018)
The use of stable water isotopes as 18O and 2H are widely used in the last 50 years as tracer in climatic and hydrological studies. Stable water isotopes have slightly different physical properties and require different latent energy for phase changes, so the concentration of water isotopes varies during water phase changes, which is known as fractionation. Specifically in the tropics, the stable water isotopes have a very particular behavior unlike other regions, by the influence of large rainfalls amount, temperature and relative humidity. Cuba is an inland in the middle of the Caribe Sea, where studies about isotopic characterization of precipitations have never been made. In order to understand and explain some issues related to the isotopic behavior of precipitation in this inland, the research work was developed making use of data from that area. The general objective of this research proposal is to characterize the isotopic composition of rainfall in west of Cuba, including the demonstration of the vegetation influence in rainfall isotopic composition, and to determine mathematical models that describe the relationship between rainfall amount, intensity and isotopic composition for future paleoclimatic studies there. Data from the Global Network of Isotopes in Precipitation (GNIP) of the International Atomic Energy Agency (IAEA) were used. Thus, the thesis was developed in three chapters of contents. The first topic addressed was in relation to demonstrate the isotopic fractionation resulting from transpiration by a green canopy. As results, it was shown that transpiration is a fractional process with respect to water isotopes. The magnitude of this fractionation is determined by environmental factors, such as soil water content, rainfall amount, temperature, and the relative humidity. The environmental factors influence the behavior of such important variables as stomatal aperture, the different diffusion resistances, and the kinetic fractionation. Then were proposed eight mathematical models that describes the relationship between rainfall isotopic composition, amount and erosivity for paleoclimatic studies. The trend founded in this research is that months with highest rainfall erosivity were less heavy isotopically. ?2H and ?18O were negatively correlated with erosivity and with the rainfall amount. The rainfall amounts were the higher negative correlation with the isotopic composition for this tropical region. In the third chapter, finally, it was evaluated if even Cuba being an island could be seen the classic effects of the isotopic hydrology as, continentality, rainfall amount and seasonality. As results, rainfalls in western Cuba are in general isotopically enriched in ?18O and ?2H in comparison with other regions at higher latitudes. The annual mean values for ?18O vary between (1 to -8) ? and for ?2H between (15 to -40) ?. Nevertheless, there is marked seasonal behavior, being the rainfalls heavier in winter and more depleted in summer, showing the established patterns for tropical region. The influence of the air masses movement on the rainfall isotopic behavior could be affirming the presence of the continental effect